PANDEMI DAN PANGGILAN BERKOMPASIO DALAM TERANG INJIL LUKAS 16:19-31: (Sebuah Implikasi dari Katekese Paus Fransiskus tentang Pandemi) - Anselmus D. Atasoge; Scolastika Lelu Beding (STP Reinha Larantuka, 2021)
The pandemic covid-19 had a tremendous, alarming, and confusing shock effect that in turn presents an unhappy situation. This situation is evocative and calling on the people to address it, including the church through pastoral reflections and social actions. Using the approach of literature studies and field observations, this paper tries to explore the basic spirit of biblis as a basic in building compassio (concerns and follow-up actions that accompany it) to those most vulnerable to the pandemic covid-19. This paper is a follow-up implication of Pope Francis catechism about